2012
DOI: 10.1002/rcm.6258
|View full text |Cite
|
Sign up to set email alerts
|

A survey of useful salt additives in matrix‐assisted laser desorption/ionization mass spectrometry and tandem mass spectrometry of lipids: introducing nitrates for improved analysis

Abstract: The recommended choice of additive depends on the desired outcomes of the experiment to be performed (MS or MS/MS). Nitrates are found to be particularly useful additives for lipid analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 50 publications
2
36
0
Order By: Relevance
“…In agreement with this, Gidden et al reported that the yield of DAG‐like ions can be significantly reduced under strongly alkaline preparation conditions (1 M NaOH or 14 M NH 3 ) which seem to prevent the initial generation of unstable protonated TAGs . By contrast, NaCl addition neither resulted in pronounced reduction of protonated lipids nor in the prevention of promptly generated lipid fragments . Gidden et al speculated that base addition scavenges most of the free H + ions donated by the used matrix 2,5‐dihydroxybenzoic acid (DHB) thereby reducing the amount of initial analyte protonation.…”
mentioning
confidence: 85%
See 1 more Smart Citation
“…In agreement with this, Gidden et al reported that the yield of DAG‐like ions can be significantly reduced under strongly alkaline preparation conditions (1 M NaOH or 14 M NH 3 ) which seem to prevent the initial generation of unstable protonated TAGs . By contrast, NaCl addition neither resulted in pronounced reduction of protonated lipids nor in the prevention of promptly generated lipid fragments . Gidden et al speculated that base addition scavenges most of the free H + ions donated by the used matrix 2,5‐dihydroxybenzoic acid (DHB) thereby reducing the amount of initial analyte protonation.…”
mentioning
confidence: 85%
“…Standard MALDI‐TOF mass spectra (i.e., without sophisticated sample purification) of physiological (phospho)lipid samples are normally dominated by the simultaneous presence of proton and sodium adducts of the individual lipids in the positive ion mode . Division of a lipid into more than one detectable species can hardly be avoided but is undesirable since the sensitivity is reduced and the presence of different adducts can complicate unequivocal peak assignments . However, in some cases the diversity is reduced by the absence of protonated lipid species: for instance, TAGs never occur as protonated but exclusively as cationized (typically sodiated) ions in MALDI‐TOF mass spectra .…”
mentioning
confidence: 99%
“…However, their investigations were only limited to abundant PCs. 7 Another way for reducing complexity was employing desalting chemicals in MALDI MS analyses. For example, sol-gel/ crown ether hybrid material was used to reduce the sodium adduct ion signals of oligonucleotides.…”
Section: Introductionmentioning
confidence: 99%
“…The sodium ion appeared to have played an important role in generating intense peaks of head group fragments as well as contributing to high yield in lipid extraction due to its inert chemical property in comparison to commonly used ammonium salt. Other metal ions such as cesium which, like sodium, has only one stable isotope, can be further exploited for enhanced sensitivity in lipid profiling 38 . Although the presence of lysyl- and alanyl-PEs appeared to be accidentally introduced in the lipid drying process, we did have established a sensitive enough lipid profiling method to rule out their biological relevance in B. subtilis .…”
Section: Discussionmentioning
confidence: 99%